Equity Price Dynamics Before and After the Introduction of the Euro: A Note - Yin-Wong Cheung; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2001)
Daily data from the German and U.S. equity markets before and after the introduction of the Euro are used to study the effect of exchange rate regime choices on equity markets. It is found that, since the introduction of the Euro, the volatility and the persistence of the German stock index have fallen significantly relative to those of the U.S. index. However, the switch in exchange rate arrangement appears to have no significant implication for the causal relationships - both the mean and variance causalities - between the two equity markets.
Keywords: G15; 330